1992
DOI: 10.1038/cr.1992.12
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular levels of calmodulin are increased in transformed cells

Abstract: By using Hoechst 33342, rabbit anti calmodulin antibody,FITC-labeled goat anti rabbit IgG and SR101(sulfo rhodamine 101)simultaneously to stain individual normal and transformed cells, the microspectrophotometric analysis demonstrated that 3 markers which represented the nucleus , calmodulin and total protein respectively, could be recognized in individualj cells without interference. The phase of the cell cycle was determined by DNA content (Hoechst 33342). We found that in transformed cells (NIH3T3) tsRSV-LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is a common observation for tumor cells to express higher levels of CaM which complements the raised levels of cytosolic Ca 2+ ions relative to benign tissues [ 356 , 357 , 358 , 359 , 360 ]. Although it was contended that this observation was cell type-, culture condition-, or transformation agent-specific, Wang et al (1992) confirmed a significant increase in CaM levels at the individual cell level between transformed and normal cells during G1 to S phase transition [ 361 ]. It was further validated that the surge in CaM levels was specific to cellular transformation and not due to a rise in total intracellular protein during cell cycle progression.…”
Section: Redistribution Of Intracellular Ca 2+ and Hijack Of Its Regulatory Machinery In Cancer Cellsmentioning
confidence: 99%
“…It is a common observation for tumor cells to express higher levels of CaM which complements the raised levels of cytosolic Ca 2+ ions relative to benign tissues [ 356 , 357 , 358 , 359 , 360 ]. Although it was contended that this observation was cell type-, culture condition-, or transformation agent-specific, Wang et al (1992) confirmed a significant increase in CaM levels at the individual cell level between transformed and normal cells during G1 to S phase transition [ 361 ]. It was further validated that the surge in CaM levels was specific to cellular transformation and not due to a rise in total intracellular protein during cell cycle progression.…”
Section: Redistribution Of Intracellular Ca 2+ and Hijack Of Its Regulatory Machinery In Cancer Cellsmentioning
confidence: 99%